Genetic diversity and population structure of Anopheles triannulatus s. l. in the department of Córdoba, Colombia, using DNA barcoding - María Atencia; Angie Toro-Cantillo; Richard Hoyos-López (Biomédica: revista del Instituto Nacional de Salud, 2018)
Introduction: Anopheles triannulatus is not incriminated as a vector of malaria transmission in Colombia despite recent reports of infection with Plasmodium spp. in populations related to the northwestern and southeastern lineages. Genetic diversity can delimit information about gene flow and population differentiation in localities with malaria. Objective: To estimate the genetic diversity of An. triannulatus in five municipalities with high and low incidence of malaria in the department of Córdoba. Materials and methods: The entomological collections were done between August and November, 2016, in Tierralta, Puerto Libertador, Montelíbano, Sahagún, and Planeta Rica. We used the COI barcoding fragment as molecular marker. The genetic analysis included the estimation of genetic parameters such as the diversity haplotype, the genetic structure, the gene flow, the Tajima’s D test, the haplotype network, and the phylogenetic relationship. Results: We obtained 148 sequences with a length of 655 nucleotides of the COI gene, from which we derived 44 haplotypes. The H2 and H21 haplotypes were the most frequent in the populations. The values of the Tajima’s D test were negative and not significant (p>0.10). The genetic structure index (FST=0.01427) and the gene flow (Nm=17.27) evidenced no differentiation between sampled populations due to the high exchange of migrants. Using phylogenetic inferences and the haplotype network, we identified one single species without geographic differentiation or lineages in the geographic range studied. Conclusions: The genetic diversity calculated for An. triannulatus in this context indicated stable populations in constant exchange.